في تعليم مهارة القراءة في المدرسة المتوسطة الإسلامية الحكومية باتو (Index Card Match) تأثير استخدام مطابقة بطاقة الفهرس - Thaha, Qashdina Alya; Machmudah, Umi (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
ABSTRACT In this study, researchers used Index Card Match in learning reading skills for class VII MTsN Batu. The aims of this study were: (1) To find out how the application of learning reading skills by using Index Card Match at MTsN Batu. (2) To find out the effectiveness of using Index Card Match in learning reading skills at MTsN Batu. This study uses experimental method with the type of Quasi Experimental Design. The results of this study are: (1) The application of learning reading skills by using Index Card Match can help students understand lessons easily. These results were obtained from the results of observations in the experimental class which were higher than the control class and the results of the questionnaire obtained 89.37% which was a high result. (2) The use of Index Card Match in teaching reading skills for class VIII students at MTsN Batu is effective. Based on the results, the average of the experimental group was 56.3617, which was greater than the average of the control group, 39.1364. The results of the t-test obtained a significant value = 0.003 less than 0.05, and the results of t count 3.120 were greater than t table 1.999, so H1 was accepted and Ho was rejected. Keywords: Learning Reading Skills, Index Card Match ملخص في هذه البحث، استخدمت الباحثة مطابقة بطاقة الفهرس في تعليم مهارة القراءة للفصل الثامن في المدرسة المتوسطة الإسلامية الحكومية باتو. أهداف هذا البحث هي: (1) لمعرفة كيف تطبيق تعليم مهارة القراءة باستخدام مطابقة بطاقة الفهرس في المدرسة المتوسطة الإسلامية الحكومية باتو. (2) لمعرفة فعالية استخدام مطابقة بطاقة الفهرس في تعليم مهارة القراءة في المدرسة المتوسطة الإسلامية الحكومية باتو. استخدمت الباحثة في هذا البحث بمنهج تجربي في شكل شبه تجريبي. نتائج هذا البحث هي: (1) أن تطبيق تعليم مهارة القراءة باستخدام مطابقة بطاقة الفهرس يساعد الطلاب على فهم الدرس بسهولة. تم الحصول على هذه النتائج من نتائج الملاحظة في المجموعة التجريبية كانت أعلى من المجموعة الضبطة وحصلت نتائج الاستبيان على 89.37٪ وهي من نتيجة عالية. (2) أن استخدام مطابقة بطاقة الفهرس في تعليم مهارة القراءة لطلاب الصف الثامن في المدرسة المتوسطة الإسلامية الحكومية باتو فعال. بناء على متوسط النتائج المجموعة التجريبية 56.3617 أكبر من متوسط المجموعة الضابطة 39.1364. وحصلت نتائج اختبار t على قيمة معنوية = 0.003 أصغر من 0.05 ، ونتائج عدد-t 3،120 أكبر من جدول-t 1،999، بحيث تم H1 مقبول وتم Ho مرفوض. الكلمات المفتاحية: تعليم مهارة القراءة، مطابقة بطاقة الفهرس